Wh-ex-situ in Mandarin Chinese: Mapping Between Information Structure and Split CP - Pan, Victor Junnan (Linguistic Analysis, 2014)
This paper examines the so-called wh-ex-situ phenomenon in Mandarin Chinese. It shows that there are four different types of wh-ex-situ in the left-periphery of Mandarin: Type I: extracted wh-topic, Type II: extracted wh-focus, Type III: base-generated wh-topic and Type IV: base-generated wh-focus. This differs from preceding accounts which analyze all ex-situ wh-phrases either as topics (cf. Tang 1988, Wu 1999) or as foci (cf. Cheung 2008, 2014). These four types display different syntactic and semantic properties. While wh-topics (extracted and base-generated) must be D-linked and obey locality constraints as well as the “episodic eventuality” constraint (cf. Zhang 2002), ex-situ wh-foci do not. However, the four types all satisfy general semantic constraints on interrogatives. Within the split-CP architecture in Chinese, ex-situ wh-topics and ex-situ wh-foci occupy different positions, TopP being higher than FocP.
Keywords: cleft focus; left periphery; Mandarin Chinese; topicalization; wh-ex-situ